2021
DOI: 10.3389/fneur.2021.713366
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Short-Term Spinal Cord Stimulation and Peripheral Nerve Stimulation for the Treatment of Trigeminal Postherpetic Neuralgia in Elderly Patients

Abstract: Objective: We aimed to report on the use of short-term high cervical spinal cord stimulation (SCS) combined with peripheral nerve stimulation (PNS) to successfully treat trigeminal postherpetic neuralgia (TPHN) affecting the V2 and V3 divisions. We also sought to use a novel PNS approach to the maxillary nerve next to the external opening of the foramen rotundum (FR) to treat TPHN at the V2 division.Method: Two elderly patients successfully treated with different neuromodulation methods for TPHN are presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…More broadly, the treatment of spinal cord stimulation includes SCS and st-SCS whose electrodes are placed percutaneously to the spinal epidural for 2 weeks. st-SCS was firstly used clinically to ease pain (16,17), and it also used as experimental treatment to test for response of patients with pain to SCS. If there is significant analgesia, electrodes of SCS will be permanently implanted a few weeks later to maintain control of pain symptoms (18).…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, the treatment of spinal cord stimulation includes SCS and st-SCS whose electrodes are placed percutaneously to the spinal epidural for 2 weeks. st-SCS was firstly used clinically to ease pain (16,17), and it also used as experimental treatment to test for response of patients with pain to SCS. If there is significant analgesia, electrodes of SCS will be permanently implanted a few weeks later to maintain control of pain symptoms (18).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term spinal cord stimulation (St-SCS) was first used for pain relief and has become an indispensable treatment means for patients with early-stage pain (39)(40)(41). In recent years, with more extensive st-SCS investigations, it has been used in the recovery of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…1 In most cases, single mode of neuromodulation is applied to seek pain relief; recently, emerging evidence has demonstrated that combination of distinct pattern of modulatory strategy can provide satisfactory control of neuropathic pain. [4][5][6] Here, we present a case of severe lower limb pain caused by postherpetic neuralgia. A new dual function DRG stimulator was implanted to provide DRG electrical stimulation and pulsed radiofrequency neuromodulation.…”
Section: Introductionmentioning
confidence: 99%
“… 1 In most cases, single mode of neuromodulation is applied to seek pain relief; recently, emerging evidence has demonstrated that combination of distinct pattern of modulatory strategy can provide satisfactory control of neuropathic pain. 4 6 …”
Section: Introductionmentioning
confidence: 99%